Ozone at low concentration modulates microglial activity in vitro: A multimodal microscopy and biomolecular study. Issue 12 (21st September 2022) - Lacavalla, Maria Assunta; Inguscio, Chiara Rita; Cisterna, Barbara; Bernardi, Paolo; Costanzo, Manuela; Galiè, Mirco; Scambi, Ilaria; Angelini, Osvaldo; Tabaracci, Gabriele; Malatesta, Manuela
Abstract: Oxygen‐ozone (O2 ‐O3 ) therapy is an adjuvant/complementary treatment based on the activation of antioxidant and cytoprotective pathways driven by the nuclear factor erythroid 2‐related factor 2 (Nrf2). Many drugs, including dimethyl fumarate (DMF), that are used to reduce inflammation in oxidative‐stress‐related neurodegenerative diseases, act through the Nrf2‐pathway. The scope of the present investigation was to get a deeper insight into the mechanisms responsible for the beneficial result of O2 ‐O3 treatment in some neurodegenerative diseases. To do this, we used an integrated approach of multimodal microscopy (bright‐field and fluorescence microscopy, transmission and scanning electron microscopy) and biomolecular techniques to investigate the effects of the low O3 concentrations currently used in clinical practice in lipopolysaccharide (LPS)‐activated microglial cells human microglial clone 3 (HMC3) and in DMF‐treated LPS‐activated (LPS + DMF) HMC3 cells. The results at light and electron microscopy showed that LPS‐activation induced morphological modifications of HMC3 cells from elongated/branched to larger roundish shape, cytoplasmic accumulation of lipid droplets, decreased electron density of the cytoplasm and mitochondria, decreased amount of Nrf2 and increased migration rate, while biomolecular data demonstrated that Heme oxygenase 1 gene expression and the secretion of the pro‐inflammatory cytokines, Interleukin‐6, and tumor necrosis factor‐ α augmented. O3 treatment did not affect cell viability, proliferation, and morphological features of both LPS‐activated and LPS + DMF cells, whereas the cell motility and the secretion of pro‐inflammatory cytokines were significantly decreased. This evidence suggests that modulation of microglia activity may contribute to the beneficial effects of the O2 ‐O3 therapy in patients with neurodegenerative disorders characterized by chronic inflammation. Highlights: Low‐dose ozone (O3 ) does not damage activated microglial cells in vitro Low‐dose O3 decreases cell motility and pro‐inflammatory cytokine secretion in activated microglial cells in vitro Low‐dose O3 potentiates the effect of an anti‐inflammatory drug on activated microglial cells Abstract : Low‐dose ozone (O3 ) does not damage activated microglial cells in vitro, but is able to decrease cell motility and pro‐inflammatory cytokine secretion, and potentiate the effect of anti‐inflammatory drugs. Modulation of microglia activity may contribute to the beneficial effects of O3 therapy in patients with neurodegenerative disorders characterized by chronic inflammation.